2016
DOI: 10.1111/medu.13086
|View full text |Cite
|
Sign up to set email alerts
|

Thrive or overload? The effect of task complexity on novices’ simulation-based learning

Abstract: Reduced task complexity was associated with superior LP performance and lower cognitive load during skill acquisition and retention, but mixed results on transfer to a more complex task. These results indicate that task complexity is an important factor that may mediate (via cognitive overload) the relationship between instructional design elements (e.g. fidelity) and simulation-based learning outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 71 publications
(172 reference statements)
4
56
0
1
Order By: Relevance
“…6 Recent evidence suggests that reduced task complexity in procedural skills training for novice learners is associated with superior task performance and lower cognitive load during the learning phase, but with mixed results on transfer of learning. 11 These results indicate that task complexity, regulated through patient characteristics and environment features, plays an important role in simulation-based learning outcomes. However, these conclusions can hardly be generalised to non-procedural skills training because the process of skill acquisition may differ.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…6 Recent evidence suggests that reduced task complexity in procedural skills training for novice learners is associated with superior task performance and lower cognitive load during the learning phase, but with mixed results on transfer of learning. 11 These results indicate that task complexity, regulated through patient characteristics and environment features, plays an important role in simulation-based learning outcomes. However, these conclusions can hardly be generalised to non-procedural skills training because the process of skill acquisition may differ.…”
mentioning
confidence: 91%
“…The authors also revealed that a lack of prior experience and the need to integrate multiple skills in one scenario contribute to increasing the perception of task complexity . Recent evidence suggests that reduced task complexity in procedural skills training for novice learners is associated with superior task performance and lower cognitive load during the learning phase, but with mixed results on transfer of learning . These results indicate that task complexity, regulated through patient characteristics and environment features, plays an important role in simulation‐based learning outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…It has been utilised to generate instructional principles for designing anatomical multimedia and generalisable design guidelines for medical education . Further, CLT has served as a useful lens when analysing medical training methods …”
Section: Introductionmentioning
confidence: 99%
“…In other words, if it looks like the ‘real thing’, it should transfer to the clinical setting. Recently, there has been discussion among simulation experts and educators about whether greater physical fidelity really is important for psychomotor development and skill attainment 4. Researchers found higher task complexity may increase cognitive load and worsen performance among novices and early learners.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found higher task complexity may increase cognitive load and worsen performance among novices and early learners. Reduced task complexity was associated with superior performance 4. This raises the question of how does physical fidelity impact cognitive skill development?…”
Section: Introductionmentioning
confidence: 99%